Assessing the scale of trust from knowledge sharing perspective: CFA approach - Rahman , Muhammad Sabbir; Anwar, Md. Aftab; Afrin, Sharmina (School of Business, Uttara University, Dhaka, Bangladesh, 2016)
Trust has been recognized as one of the primary antecedents in the determination of the success of staff knowledge sharing behavior. The aim of this inquiry is to empirically examine the construct of trust from the perspective of knowledge sharing behavior from the non-academic staff of higher learning institutions. In total, 250 valid samples were collected via self-administered survey procedure from the non-academic staff of different public and private higher learning institutions in Malaysia. Confirmatory factor analysis (CFA) was employed to examine the construct. The results revealed the significant items of trust factor in regards of non-academic staff knowledge sharing behavior from the perspective of higher learning institutions. The proposed model of trust has been empirically tested for unidimensionality, reliability and validity using CFA. This study is one of the ﬁrst attempts to speciﬁcally focus on trust constructs in aspects of knowledge sharing behavior under the scope of higher learning institutions in Malaysia.